SISTEM PAKAR PENDIAGNOSA PENYAKIT DIABETES MELITUS MENGGUNAKAN FORWARD CHAINING - Depi Trisnawati; Mariana Windarti; Istri Sulistyowati; Fajar Budi Hartono (Journal of Computer Science and Technology, 2022)
Diabetes is a disease that causes death which is quite high in the world, even in Indonesia, this is indicated by the position of Indonesia with the highest number of diabetic patients, which is 7th out of 10 countries. Diabetes Mellitus is also a chronic disease that is a public health problem in Indonesia. By 2020, the number of diabetes attacks will reach 18 million. The increasing use of computer technology causes the rapid flow of information and communication from one place to another. One application of technology is an expert system. This expert system is used for early detection of the type of disease suffered by the patient based on the symptoms caused without having to go to the doctor. In this study, an expert system for diagnosing diabetes mellitus will be designed. The method used is the forward chaining inference method and Microsoft Visual FoxPro 9.0 software. The forward chaining method works by analyzing the facts obtained from the input based on the rules stored in the database to get a conclusion. This expert system for diagnosing diabetes mellitus is used by the community as a tool for early detection without having to consult directly with a doctor. The conclusion or solution obtained from this expert system is that the user is predicted to have diabetes or does not have mild or secondary diabetes along with the results of the diagnosis according to the solution provided by the system